Why are Websites Co-linked? The Case of Canadian Universities - Vaughan, Liwen; Kipp, Margaret E.I; Gao, Yijun (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
A random sample Web pages that linked to a pair of Canadian universities was retrieved. The content of the page as well as the context of the link were manually examined to record the following variables: language, country, type of Website, and the reason for co-linking. Un échantillon aléatoire de pages web reliées à une paire d’universités canadiennes a été repéré. Le contenu de la page, aussi bien que le contexte du lien ont été manuellement examinés pour enregistrer les variables suivantes : langue, pays, type de site web et raison du co-lien.